Preliminary Financial Risk Management Strategies for Commercial Banks in the Era of the Digital Rupiah - Rantelino, Echika; Tumewu, Ferdinand (Universitas Sam Ratulangi, 2026)
This study examines preliminary financial risk management strategies for Indonesian commercial banks in response to the proposed Digital Rupiah. Using a qualitative-exploratory approach, it applies comparative analysis of CBDC implementations in China, India, Nigeria, the Bahamas, and Brazil, supported by crisp-set Qualitative Content Analysis (sQCA). The study integrates ISO 31000, Basel II, Enterprise Risk Management (ERM), Strategic Risk Management (SRM), and Dynamic Capabilities Theory (DCT). Findings show that the Digital Rupiah’s hybrid, two-tier, retail-oriented design creates multidimensional risks, including liquidity and disintermediation risk, operational and cybersecurity risk, compliance risk, and strategic business model risk. These risks stem from shifts in deposit behavior, technological dependence, and financial intermediation. The study proposes integrated mitigation strategies, including strengthening liquidity management, enhancing digital capabilities, improving compliance systems, and transforming business models. It concludes that banks must adopt a holistic and forward-looking risk management approach to remain resilient in a digital financial ecosystem. Keywords: Central Bank Digital Currency, Digital Rupiah, Financial Risk Management, Commercial Bank, Risk Management.